The phonetics and phonology of the intonation of Irish dialects - Dalton, Martha (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2008)
This study is concerned with describing the intonation of the major dialects of Irish, comprising the Donegal dialect of Gaoth Dobhair, the Connaught dialects of Cois Fhairrge, Inis Oírr and Mayo, and the Munster dialect of Baile an Fheirtéaraigh in West Kerry. The study is based on phonological and phonetic analysis of read speech, across three grammatically different sentence types: declaratives, wh-questions and yes/no-questions. The first aim of the study is to provide a cross-dialect account of the tonal inventory of the major dialects of Irish. This analysis is carried out within the Autosegmental-Metrical (AM) framework of intonational analysis. To begin, a preliminary inventory of the pitch accents of each dialect is established. The findings indicate that the divide in the phonological structure of each of the dialects is, to some extent, linked to the geographical location of each of the dialects. The second aim of the study is to provide a more detailed description of how the major tonal categories of the Irish dialects are timed, in relation to the segmental or syllabic string. The purpose here is to capture some of the finer phonetic differences in pitch accent realisation. The results from this peak timing analyses show major alignment differences between the major dialects of Irish, and more subtle differences in peak timing among structurally similar dialects. The timing differences among superficially more similar dialects provides an insight into how these phonologically similar dialects can be perceived as different by local listeners.
Keywords: Language and Communication Studies, Ph.D.; Ph.D. Trinity College Dublin